2011
DOI: 10.1126/scitranslmed.3002166
|View full text |Cite
|
Sign up to set email alerts
|

Protein Interactome Reveals Converging Molecular Pathways Among Autism Disorders

Abstract: To uncover shared pathogenic mechanisms among the highly heterogeneous autism spectrum disorders (ASDs), we developed a protein interaction network that identified hundreds of new interactions among proteins encoded by ASD-associated genes. We discovered unexpectedly high connectivity between SHANK and TSC1, previously implicated in syndromic autism, suggesting that common molecular pathways underlie autistic phenotypes in distinct syndromes. ASD patients were more likely to harbor CNVs that encompass network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(220 citation statements)
references
References 56 publications
5
215
0
Order By: Relevance
“…SMARCA2 encodes a protein that belongs to the FMRP complex, deficient in fragile X syndrome and is involved in a large network of interactions with other ASD related proteins such as TSC1 and NLGN3. 28,29 To test the hypothesis that additional variants in SMARCA2 and/or DOCK8 contribute to autism, we sequenced the exons of these two genes in the patient with the 9p deletion, but no rare, possibly pathogenic variants were identified. Recently, heterozygous nonsynonymous mutations or partial deletions in SMARCA2 were identified as the cause of Nicolaides-Baraitser syndrome, an autosomal dominant condition with syndromic ID.…”
Section: Discussionmentioning
confidence: 99%
“…SMARCA2 encodes a protein that belongs to the FMRP complex, deficient in fragile X syndrome and is involved in a large network of interactions with other ASD related proteins such as TSC1 and NLGN3. 28,29 To test the hypothesis that additional variants in SMARCA2 and/or DOCK8 contribute to autism, we sequenced the exons of these two genes in the patient with the 9p deletion, but no rare, possibly pathogenic variants were identified. Recently, heterozygous nonsynonymous mutations or partial deletions in SMARCA2 were identified as the cause of Nicolaides-Baraitser syndrome, an autosomal dominant condition with syndromic ID.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mice lacking the polysialyltransferase that regulates NCAM PSA in adulthood (PST or ST8SiaIV) also exhibit social deficits and these become even more severe in mice lacking the developmental enzyme (STX or ST8SiaII) (Calandreau et al, 2010). This observation is also of interest in that may the abnormal expression of autism susceptibility genes have been associated with cell adhesion molecules involved in synapse signaling and glycosylation events (Pinto et al, 2010;Ye et al, 2010;Sakai et al, 2011).…”
Section: Construct Validity Of Vpa Model Of Asdmentioning
confidence: 99%
“…New monogenic ID and ASD syndromes are continuously being discovered, and some of these reveal specific molecular links between ID/ ASD and more language-specific disorders. Two recentlydiscovered syndromes are caused by haploinsufficiency of transcription factors that are known to directly interact with FOXP2 (Li et al 2004;Sakai et al 2011;Deriziotis et al 2014). One syndrome results from mutations of FOXP1, a paralog of FOXP2 which shows partially overlapping expression in brain regions including the striatum (Ferland et al 2003).…”
Section: Intellectual Disability and Autism Spectrum Disordersmentioning
confidence: 99%
“…Several studies have identified putative members of this FOXP2 molecular network (Coutinho et al 2011;Clovis et al 2012;Shi et al 2013;Spiteri et al 2007;Vernes et al 2007;Konopka et al 2009;Vernes et al 2011;Li et al 2004;Chokas et al 2010;Sakai et al 2011;Zhou et al 2008). In previous sections we have discussed the relationship of the FOXP2 target, CNTNAP2, and the FOXP2 interacting proteins, TBR1 and FOXP1, to communication disorders.…”
Section: Epilepsy-aphasia Spectrum Disordersmentioning
confidence: 99%